Kevin Bloom and Richard Poplak, Continental Shift: A Journey into Africa’s Changing Fortunes (Historia, 2021)
This book by two well-respected South African journalists is, in many ways, a coming-of-age retelling of an intricate and unexpected journey through a continet that is itself experiencing some growing pains. A write-up of a project that spans nine years and 10 countries (Namibia, Botswana, Zimbabwe, Nigeria, Democratic Republic of the Congo, Ethiopia, South Sudan and Central African Republic) this "biography" of an adolescent Africa has evidently battled through a number of existential crises before taking on the form that is presented to the reader in this publication almost a decade after its inception.
Keywords: coming-of-age; Kevin Bloom; Richard Poplak; Africa